Pengaruh Brand Image dan Label Halal terhadap Keputusan Pembelian Produk Wardah pada Mahasiswa FEBI UIN STS Jambi - Netty Purnama Sari; Habriyanto Habriyanto; Muthmainnah Muthmainnah (ARZUSIN, 2025)
Consumer purchase decisions regarding halal cosmetic products have become increasingly relevant amid rising religious awareness and intense competition within the beauty industry. However, understanding the contribution of brand image and halal labeling remains limited, particularly among university students. This study aims to analyze the influence of brand image and halal labels on purchasing decisions for Wardah products among students of the Faculty of Islamic Economics and Business (FEBI) at UIN Sulthan Thaha Saifuddin Jambi. A quantitative survey method was employed, involving 100 students selected through simple random sampling using Slovin’s formula. The research instrument was a Likert-scale questionnaire, while data were analyzed using multiple linear regression with t-tests, F-tests, and the coefficient of determination. The results show that brand image has a positive and significant effect on purchase decisions (sig. 0.002 < 0.05; coefficient 0.482). Halal labeling also has a positive and significant effect (sig. 0.024 < 0.05; coefficient 0.495). Simultaneously, both variables significantly affect purchase decisions (sig. 0.001 < 0.05; F = 34.453; R² = 0.426). The study concludes that brand image and halal labels are key determinants influencing FEBI UIN STS Jambi students’ decisions to purchase Wardah products, with implications for producers to strengthen brand image and ensure halal certification as effective marketing strategies.